Six-month depot formulation of leuprorelin acetate in the treatment of prostate cancer - Rajni Sethi (Dove Medical Press, 2009)
Rajni Sethi, Nicholas SanfilippoDepartment of Radiation Oncology, New York University Langone Medical Center, New York, NY, USAAbstract: Hormonal deprivation therapy is well established for the treatment of locally advanced and metastatic prostate cancer, as well as the adjuvant treatment of some patients with localized disease. Long-acting gonadotropin releasing hormone (GnRH) agonists have become a mainstay of androgen deprivation therapy, due to their efficacy, tolerability, and convenience of use. One-month, 3-month, and 4-month depot leuprorelin formulations are well established and widely used to this end. Recently, a 6-month depot leuprorelin has been approved for use in advanced and metastatic prostate cancer patients. With similar efficacy and side effect profiles to earlier formulations, 6-month depot leuprorelin is a convenient treatment option for these patients. This review will highlight the role of GnRH agonists in the treatment of prostate cancer with a focus on the clinical efficacy, pharmacology, and patient-focused outcomes of the newer 6-month 45 mg depot leuprorelin formulation in comparison to available shorter-acting products.Keywords: prostate cancer, leuprorelin, hormonal deprivation therapy